A Window to Toxoplasma gondii Egress - Lucio Ayres Caldas (Pathogens, 2018)
The Toxoplasma gondii cellular cycle has been widely studied in many lifecycle stages; however, the egress event still is poorly understood even though different types of molecules were shown to be involved. Assuming that there is no purpose or intentionality in biological phenomena, there is no such question as “Why does the parasite leaves the host cell”, but “Under what conditions and how?”. In this review we aimed to summarize current knowledge concerning T. gondii egress physiology (signalling pathways), structures, and route.